Goniometric Measurement of Limb Stiffness: Validation of a Potential Predictor of Tendon Healing. (September 2015) - Tucker, R.; Jacklin, B.D.; Gillespie, S.; Vaughan, L.; Fiske‐Jackson, A.R.; Smith, R.K.
Abstract : Reasons for performing study: Injury to the superficial digital flexor tendon (SDFT) is common in equids, with a high risk of re‐injury associated with changes in tendon stiffness. In vivo measurement of limb stiffness has been shown to correlate with tendon stiffness after injury [1] but requires kinematic analysis which is impractical in a clinical setting. We have developed a simple system for measuring limb stiffness statically, which could be used as a tool for monitoring SDFT healing. Objectives: To validate a goniometric measurement of limb stiffness. Study design: Cross sectional study. Methods: Initially, forelimb stiffness indices were determined at the walk for 6 equids using a validated kinematic analysis [1]. Limb stiffness indices were then calculated using portable floor scales to record ground reaction force (GRF), and an electrogoniometer to record metacarpophalangeal joint angle. Goniometric limb stiffness indices were subsequently measured in 11 horses ranging from 2 to 20 years of age, with no clinical evidence of SDFT injury. Strength and significance of correlation and agreement between the measurement methods was assessed and association between limb stiffness, limb (left vs. right), weight and age of horse and were calculated. Results: There were strong positive correlations between GRF and joint angle (R 2 = 0.98) and between the static and kinematic methods (R = 0.78, P<0.01). There was a positive correlation between limb stiffness and weight (R 2 = 0.85, P<0.01), but no association with age or limb. Conclusions: This study validated the measurement of limb stiffness in a clinical setting. The positive correlation of limb stiffness and weight supports the theory of an optimised limb spring [2] for energy‐efficient cursorial locomotion which may, in turn, provide a clinically‐relevant measure of running efficiency and therefore the quality of tendon healing post injury. Ethical animal research: Owner consent was obtained.Source of funding: None.Competing interests: None declared.